Herbal Supplement Consumption Trends Among Adolescents: Nutritional Perspectives and Safety of Use - Balfas, Rifqi Ferry (Oshada, 2025)
In recent years, herbal supplement consumption among adolescents has increased significantly, in line with the rise of healthy lifestyle trends and the influence of social media. Natural-based supplements are perceived as a quick solution to improve vitality, appearance, and endurance. However, this phenomenon is often not accompanied by an adequate understanding of nutrition, product safety, and the risk of pharmacological interactions. This study aims to examine herbal supplement consumption patterns among adolescents through a literature review approach from a nutritional and safety perspective. Data sources were obtained from indexed scientific journals, official publications, and relevant studies from 2019–2024. The findings indicate that low nutritional literacy, the strong influence of online media, and weak product distribution regulations contribute to a high potential for irrational consumption. Most adolescents consume supplements without medical consultation, assuming that all natural products are safe, despite scientific evidence showing potential risks such as toxic effects, synthetic contamination, and drug interactions. Therefore, an integrated educational strategy within the education system and evidence-based digital health campaigns are needed. Synergy between the government, schools, families, and health workers is crucial for shaping safe, rational, and nutritionally appropriate consumption behavior among adolescents